Determinants of Statural Growth in European Children With Chronic Kidney Disease: Findings From the Cardiovascular Comorbidity in Children With Chronic Kidney Disease (4C) Study - Behnisch, Rouven; Kirchner, Marietta; Anarat, Ali; Bacchetta, Justine; Shroff, Rukshana; Bilginer, Yelda; Mir, Sevgi; Caliskan, Salim; Paripovic, Dusan; Harambat, Jerome; Mencarelli, Francesca; Büscher, Rainer; et al. (Frontiers in Pediatrics, 2019)
Failure of statural growth is one of the major long-term sequelae of chronic kidney disease (CKD) in children. In recent years effective therapeutic strategies have become available that lead to evidence based practice recommendations. To assess the current growth performance of European children and adolescents with CKD, we analyzed a cohort of 594 patients from 12 European countries who were followed prospectively for up to 6 years in the 4C Study. While all patients were on conservative treatment with a mean estimated glomerular filtration rate of 28 ml/min/1.73 m2 at study entry, 130 children commenced dialysis during the observation period. At time of enrolment the mean height standard deviation score (SDS) was -1.57; 36% of patients had a height below the third percentile. The prevalence of growth failure varied between countries from 7 to 44% Whereas patients on conservative treatment showed stable growth, height SDS gradually declined on those on dialysis. Parental height, pubertal status and treatment with recombinant growth hormone (GH) were positively, and the diagnosis of syndromic disease and CKD stage were negatively associated with height SDS during the observation period. Unexpectedly, higher body mass index SDS was associated with lower height SDS both at enrolment and during follow up. Renal anemia, metabolic acidosis and hyperparathyroidism were mostly mild and not predictive of growth rates by multivariable analysis. GH therapy was applied in only 15% of growth retarded patients with large variation between countries. When adjusting for all significant covariates listed above, the country of residence remained a highly significant predictor of overall growth performance. In conclusion, growth failure remains common in European children with CKD, despite improvemed general management of CKD complications. The widespread underutilization of GH, an approved efficacious therapy for CKD-associated growth failure, deserves further exploration.